A liderança de pessoas cegas em narrativas - Souza, Márcio Ramos de (2020)
Over the years, there have been discussions on the question of social, school and professional inclusion of visually impaired people. This study aims to comprehend the blind people based on their narratives, investigating their experience during their higher education and the senses attached to the possibilities of accepting, or not a leadership burden. As a building source methodology used by Flick (1992) in episodes interview and the diary of the researcher, Lewgoy and Arruda (2004). Three blind people, university students participated in the research, between the ages of 28 and 31 The research considered the principles and method of (auto)biographical research in education (Delory-Momberger 2014; Passeggi 2010, 2011 e 2016); leadership studies (Chiavenato 2005; Hunter 2006; Maxwell 2014) and principles of inclusive education, reference to the visually impaired (Amiralian 1997 e 2000; Carvalho 2004; Herculano 2004). The participants' narratives made it possible to organize the analysis into three thematic categories: "leader of myself", "servant leadership" and "qualification as a strategy for opportunities". These categories include participants' understanding of the feeling of professional devaluation and the recording of experiences in the working world. Narrative analysis reveals that the blind people value five elements in the leaderships of employees: empathy; the dialogue; cooperation; appreciation of differences and teamwork. The results of the analyses highlight the importance of listening to blind people who have attained higher education, about their expectations for the leadership of the visually impaired and the meanings they attribute to the positions of leaders, in order to deepen investigations and reflections on the rights of the person. Visually impaired in their workplace and employment based on their experience and what they say about their actual perspectives.